The corn farmers' demand for agricultural microfinance in Valencia City, Bukidnon - Marimon, Churwyn B.
Agricultural microfinance has increasingly been considered as an important tool for improving the economic lives of the poor farmers in the Philippines. This paper presents an impirical investigation on the demand and borrowing decisions of the corn farmers in Valencia City, Bukidnon. 20 Barangays were randomly selected and primary data were collected from a survey administered to 97 corn farmers. Both qualitative and quantitative analyses were applied in the study. On the qualitative part, descriptive statistics was used while on the quantitative approach, three models estimated: the logliner demand model using ordinary least square (OLS) and two choice models using multinomial and conditional logistic regression. The results revealed that in the logliner demand model, interest rate from both sources, income, age, years spent being a client of formal microfinance, distance of MFI offices from respondents' farm, land hectare, frequency of repayment problems, crop failure and educational attainment can significantly affect the corn farmers' demand for microloan. However, the latter two have counter-intuitive results. In the multinomial logit (choice) model, four borrowing options were considered and results have shown that corn farmers would decide first to borrow from an informal lender, followed by opting not to borrow, then borrowing from both sources and lastly deciding to borrow from formal sources with a probability of 37.^%, 34.4%, 20.3% and 7.65%, respectively. On the other hand, the results from the conditional logit (choice) model have not shown any in conformity with the Law of Demand. The study concluded that being a client of agricultural microfinance will have an improved farm income and still, interest rate could hinder the farmers from borrowing to these formal microfinance institutions (MFIs). Thus, some possible strategies worth considering in an attempt to balance out both ends: success in the microfinance business by these MFIs and upholding the welfare of the poor farmers.